Relationship between age and expertise with the maximum impact force of a reverse punch by shotokan karate athletes - Aguiar de Souza, V.; Marques, A. M. (Archives of Budo, 2017)
Background and Study Aim: Karate is a Japanese martial art that traditional apparatus such as the punching board (makiwara) to improve, effectiveness (stroke precision) and physical strength. However, little is known about the magnitude of the impact forces, and its connection to anthropometric and biomechanical variables. To fill this gap, the cognitive goal of this study is the knowledge about two phenomena: (i) the maximum impact force on a punching board generated by a reverse punch (gyaku-zuki) in a front stance (zenkutsu-dachi) in conditions as close as possible to the regular practice, and (ii) the relationship between anthropometric (age) and biomechanical (expertise) variables with the maximum impact force.